Clinical and psychological ground of principles of prognostication of premature delivery risk - Siusiuka, V. G.; Potapov, V. O.; Shevchenko, A. O.; Kyryliuk, O. D.; Guba, N. O.; Mosol, N. O.; Сюсюка, Володимир Григорович; Потапов, В. О.; Шевченко, Анна Олександрівна; Кирилюк, Олександр Дмитрович; Губа, Н. О.; Мосол, Н. О. (My University, 2022)
The objective: to assess the diagnostic significance of anamnestic and clinical-psychological factors and develop the prediction criteria for the threat of premature birth (PB). Materials and methods. An analysis of the data of pregnant women who were tested in the II and early III trimesters (screening is the I stage of the study) was carried out. The pregnant women were conditionally divided into two groups. The main group included 30 women whose further course of pregnancy was complicated by the threat of PB. The comparison group included 222 women without clinical manifestations of threat of PB during the current pregnancy. During the II stage of the study, the systematization of existing anamnestic and clinical-psychological factors among the examined women was performed. At the III stage, a comparative analysis of the frequency of the symptoms identified at the I stage was carried out in pregnant women in groups with the calculation of diagnostic coefficients (DC) of measures of informativeness (MI) according to formulas. Diagnostic (prognostic) tables were created for each factor, DC and MI were calculated based on the ratio of frequencies. According to the methodology for calculating the accuracy of the diagnostic decision to achieve a probability level of 95 % (p=0.05), the limit ΣDC is a constant = ±13, to achieve a probability of 99 % = ±20, to achieve a probability of 99.9% = ±30. If there is a factor in the column of the scale that is not included in the spectrum of exclusions, put a check mark in the “yes” column of the corresponding row. In the absence of such a check mark is placed in the “no” column of the corresponding row. Regarding the filling of each row, the sum of DC is calculated by adding up the indicated DCs, in the case of reaching the value of ΣDC, a preliminary diagnostic conclusion is made about the probability for threat of PB (at ΣDC = -13), which has a confidence level of 95 % (p=0.05). If the value of ΣDK = -20 is reached, a final diagnostic conclusion is made about the probability of 99 % for threat of PB (p=0.01). If the limit of the range is -13 < ΣDC < +13, the conclusion is significant because in such case its “p” is > 0.05. Results. Based on the values of DC and MI of Kullbak (valid signs), a clinical scale to predict threat of PB with a confidence level of 95 % (p=0.05) or 99 % (p=0.01) was developed. Among the informative signs (factors) for predicting of threat of PB the following factors were established: spontaneous miscarriage in the anamnesis, high personal and situational anxiety (45 points and above), IV and more pregnancies and artificial abortion in the anamnesis, as well as the level of neuroticism (16 points and above). Conclusions. It has been established that anamnestic and clinical-psychological factors, namely, miscarriage in the anamnesis, artificial abortion in the anamnesis, IV and more pregnancies, high levels of personal and situational anxiety and neuroticism, are important and effective criteria for predicting the threat of premature birth. Мета дослідження: оцінювання діагностичної значущості анамнестичних і клініко-психологічних факторів та розроблення критеріїв прогнозування загрози передчасних пологів (ЗПП). Матеріали та методи. Було проведено аналіз даних вагітних, які пройшли тестування у II та на початку III триместра (скринінг – I етап дослідження). Вагітні умовно були розподілені на дві групи. В основну групу увійшли 30 жінок, у яких подальший перебіг гестації ускладнився клінікою ЗПП. До групи порівняння включені 222 жінки без клінічних проявів ЗПП у період поточної вагітності. На IІ етапі дослідження була проведена систематизація існуючих анамнестичних і клініко-психологічних чинників серед контингенту обстежених жінок. На IІI етапі виконано компаративний аналіз частоти виникнення ознак, виділених на І етапі, у вагітних у групах з розрахунком діагностичних коефіцієнтів (ДК) мір інформативності (МІ) за формулами. Проведено формування діагностичних (прогностичних) таблиць для кожного фактора, на підставі співвідношення частот були розраховані ДК та МІ. Згідно з методологією розрахунку достовірності діагностичного рішення для досягнення рівня ймовірності 95 % (p=0,05), порогова ΣДК є константою = ±13, для досягнення ймовірності 99% = ±20, для досягнення ймовірності 99,9% = ±30. За наявності фактора у бланку шкали, яка не входить до спектра виключених, ставлять відмітку у стовпці «так» відповідного ряду. За відсутності такого відмітку ставлять у графі «ні» відповідного ряду. Щодо заповнення кожного ряду, проводять підрахунок суми ДК шляхом складання зазначених ДК, у разі досягнення значення ΣДК роблять попередній діагностичний висновок про ймовірність ЗПП (при ΣДК = -13), що має рівень достовірності 95% (p=0,05). У разі досягнення значення ΣДК = -20, роблять остаточний діагностичний висновок про ймовірність ЗПП 99 % (p=0,01). Якщо межа діапазону -13 < ΣДК < +13 – висновок не можна вважати достовірним, тому що при цьому його p>0,05. Результати. На підставі значень ДК та МІ Кульбака (валідних ознак) розроблена клінічна шкала, що дозволяє прогнозувати ЗПП з рівнем достовірності 95 % (p=0,05) або 99 % (p=0,01). Серед інформативних ознак (факторів) прогнозування ЗПП встановлені: мимовільний аборт в анамнезі, висока особистісна та ситуативна тривожність (45 балів і вище), IV і більше вагітностей та артифіціальний аборт в анамнезі, а також рівень нейротизму (16 балів і вище). Висновки. Установлено, що анамнестичні та клініко-психологічні фактори, а саме – мимовільний аборт в анамнезі, артифіціальний аборт в анамнезі, IV та більше вагітностей, високі рівні особистісної та ситуативної тривожності і нейротизму, є важливими та ефективними критеріями для прогнозування загрози передчасних пологів.
Клініко-психологічне обґрунтування принципів прогнозування загрози передчасних пологів
Сюсюка В. Г. – ORCID: 0000-0002-3183-4556; Шевченко А. О. – ORCID: 0000-0002-7883-2873; Кирилюк О. Д. – ORCID: 0000-0002-0173-5661.
Keywords: pregnancy; anamnesis; psychoemotional state; threat of premature birth; prediction criteria; вагітність; анамнез; психоемоційний стан; загроза передчасних пологів; критерії прогнозування